ALLOMETRIC MODELS TO ESTIMATE STOCKS CARBON IN THE LOWER MONTANE FORESTS IN SOUTH OF ECUADOR - Lozano Sivisaca, Deicy Carolina [UNESP]; Palacios Herrera, Byron Gonzalo; Aguirre Mendoza, Zhofre Huberto (Centro Pesquisas Florestais, Ufsm, 2018)
In Ecuador, there are montane forests of great biological importance that provide ecosystem services such as carbon storage. For this reason, we did this research for generate allometric models through by quantifying carbon in lower montane forests. We established one permanent plot of one hectare and measured all the trees with diameter at breast height (DBH1.30m) >= 5 cm. The variables that were used to generate the models were: DBH and total height (th). The tree biomass was 322.37 t ha(-1) and the estimated total carbon was 161.07 t ha(-1). In the allometric models of the arboreal stratum, the variables that were adjusted best were: DBH, DBH2 and th. The botanical family with more biomass (69.95 t ha(-1)) and carbon (34.98 t C ha(-1)) was Moraceae, which together with Lauraceae, Rubiaceae and Myristicaceae stored the 57% carbon (91.55 t C ha(-1)) in the lower montane forest. Of the 179 botanical species registered, Pseudolmedia laevigata, Nectandra reticulata, Otoba parvifolia, Vochysia paraensis, Ficus sp and Elaeagia obovata stored 51% (81 t C ha(-1)) of carbon total estimated.
Keywords: biomass; ecosystem service; Lauraceae